PWE-076 Specialist Centre Patient Volume Does Not Impact on Endoscopic Outcomes for Treatment of Barrett's Dysplasia. Results from The UK Registry. (17th August 2016) - Lipman, G; Gupta, A; Banks, M; Sweis, R; Dunn, JM; Morris, D; Smart, H; Bhandari, P; Willert, RP; Fullarton, G; Morris, AJ; Di Pietro, M; et al.
Abstract : Introduction: Endoscopic mucosal resection (EMR) followed by Radiofrequency ablation (RFA) is first line treatment for mucosal Barrett's oesophagus (BE) related neoplasia. The UK Registry collects data from patients at 28 sites undergoing RFA/EMR. We examine differences in outcomes between sites by patient volume. Methods: All visible lesions were entirely removed by EMR. Patients then underwent RFA every 3 months until all visible BE was ablated. Biopsies were taken at 12 months to assess treatment success with repeat biopsies every 6–12 months thereafter. Centres were grouped by total numbers treated; low <50, medium 50–100 & high >100 patients. Only outcomes of those who had completed treatment were analysed. Results: 675 patients completed treatment at 24 centres (median follow up 26 months), 414 at high volume (n = 5), 143 at medium volume (n = 4) & 118 at low volume centres (n = 15). There was no difference in entry criteria or demographics between groups. CR-D & CR-IM at 12 months are no different between the groups (CR-D 86–90%, CR-IM 74–81%). IM recurrence is significantly lower in high volume centres (16.1% vs 20.3% and 19.2%, Log Rank p < 0.001) but dysplasia recurrence is no different (Log Rank p = 0.12). Rescue EMR was performed less frequently in medium volume centres (0% vs high 5.3% and low volume 10%, p = 001). Conclusion: Endotherapy for Barrett's dysplasia is highly effective whatever the centre volume. The rescue EMR rate in medium volume centres is unexplained. Despite lower IM recurrence in high volume centres, dysplasia recurrence rates are not significantly different. Caseload volume of a centre in the UK Registry does not appear to affect outcome. Disclosure of Interest: None Declared